Challenges in developing in-service teacher training. Lessons learnt from two projects for teachers of Swedish in Finland - Huhtala, Anne; Vesalainen, Marjo (Apples - Journal of Applied Language Studies, 2017)
Teacher education in Finland is widely respected and of high quality. However, there is a recognised need to develop the educational continuum from pre-service education to in-service training. This article deals with challenges connected to in-service teacher training. Based on two projects, consisting of seven one-month courses for teachers of Swedish in Finland, we reflect on the challenges we encountered during the three-year process. In our research, theory and practice, but also data and methods, have been intertwined, as we have studied the phenomenon by using exploratory practice (Allwright, 2003). The projects and the study were based on a thorough literature review. During the planning phase, we identified many issues that should be taken into consideration during in-service training projects for teachers of Swedish, e.g., challenges posed by the new national core curricula and the new distribution of lesson hours, declining results in middle-long Swedish (Syllabus B1), relatively low self-reported school satisfaction, and problems linked with teachers’ professional development. In this paper, we report on challenges we encountered during the process. These included challenges connected to (a) teacher co-operation, (b) traditional vs. modern teaching methods, and (c) teachers’ language skills. Based on our research, we wish to emphasise the importance of research-based planning and implementation of in-service training, as well as a genuine connection between in-service training, teachers’ everyday work and school reality.
Keywords: In-service teacher training, Professional development , Challenges, Teachers of Swedish